Local Government Resonance on Disaster Potential Issues - Muh Resa Yudianto Suldani; Hermin Indah Wahyuni; P. Wiryono Priyotamtomo (Borong Newinera Publisher, 2023)
Ring of fire that surround Indonesia from east to the west made this country become potential vulnerable to various types of natural disasters, Morowali is a district located in central sulawesi province that one of a disaster-prone area. It is traversed by the Matano fault which connected to Palu Koro fault which is a fault with approximately 8 mm active movement per year. This study aims to see how far the local government of Morowali responds to the issue of potential disasters, consider that Morowali district is one of the areas designated by the state government as a special economic zone. This study using an exploratory case study that does not see phenomena only from problems but also in the form of social activities, groups, and organization. Niklas Luhmann's concept of resonance is the main reference in describes the interconnection between systems and the environment. Research data obtained using in-depth interviews, focus group discussions, and field observations. The informants in this study were executive and legislative board. The results show that the executive and legislative response to the issue of potential natural disasters shows the resonant capacity of two functional systems politics and economics are weak, which shows that the government's system should encourage the concept of proactive adaptation to strengthen its response to the existing potential disasters and create security for the Morowali community.